Prinsip Didaktik Pentakostal: Ekstraksi Teologis dan Pedagogis dari Paulo Freire - Pantan, Frans; Timadius, Hendrik; Pakpahan, Gernaida K. R.; Cahyono, Heru (Regula Fidei : Jurnal Pendidikan Agama Kristen, 2021)
In the past decade, Pentecostal scholars have continued to make improvements in all aspects of human life. This includes the world of education and ecclesiastical. The world of Pentecostal Education has undertaken a process of re-extraction of theology and its pedagogy. This process is carried out by absorbing the values echoed by Paulo Freire about the concept of Education which provides as much space as possible for the development of free thinking. Free thinking is meant by the spirit of social humanism with fellow human beings, not oppressing in the form of verbally or in deeds, and parallels between teachers and students. Whereas in ecclesiastical, the value of humanizing humans to understand humans as a whole is. The method used to collect data is descriptive qualitative with library studies. The results of the study found that the Freire concept was in the process of absorbing and being applied by Bethel School of Theology even though it had been modified into a Pentecostal Catechesis concept. Meanwhile, in an ecclesiastical context, GBI has adopted Freire's values in the form of humanizing training such as the Healing Movement Camp (HMC), I am a Christ Follower (SPK), and Doulos Camp. AbstrakDalam satu dekade terakhir, para cedikiawan Pentakosta terus melakukan pembenahan dalam segala aspek kehidupan umat. Termasuk didalamnya dunia Pendidikan dan gerejawi. Dunia Pendidikan pentakosta melakukan proses reekstraksi akan teologi dan pedagoginya. Proses ini dilakukan dengan menyerap nilai-nilai yang digemakan oleh Paulo Freire akan konsep Pendidikan yang memberikan ruang sebesar-besarnya untuk kepengembangan berpikir bebas. Berpikir bebas yang dimaksud adalah semangat humanisme sosial dengan sesama manusia, tidak melakukan penindasan dalam bentuk verbal maupun perbuatan, dan kesejajaran antara guru dan murid. Sedangkan dalam gerejawi, nilai memanusiakan manusia untuk memahami manusia secara utuh adalah. Metode yang digunakan untuk mengumpulkan data adalah kualitatif deskriptif dengan studi perpustakaan. Hasil penelitian menemukan bahwa konsep Freire sedang dalam proses menyerap dan aplikasi oleh Sekolah Tinggi Teologi Bethel meskipun telah dimodifikasi menjadi konsep Katekesis Pentakosta. Sedangkan dalam konteks gerejawi, GBI telah mengadopsi nilai Freire dalam bentuk pelatihan memanusiakan manusia seperti Healing Movement Camp (HMC), Saya Pengikut Kristus (SPK), dan Doulos Camp.